Prognostic Significance of Serum-Soluble Endoglin (CD105) Levels in Patients with Acute Myeloid Leukemia - Soydan, Muhammed Emin; Sincan, Gülden; Kızıltunç, Ahmet (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
We investigated the serum-soluble endoglin (CD105) levels and their prognostic significance in patients with acute myeloid leukemia (AML), given that angiogenesis, stimulated by vascular endothelial cells, is known to increase during AML development, and serum-soluble endoglin is a transmembrane protein that induces the activation and proliferation of these cells.The study included 30 newly diagnosed or relapsed AML patients followed at the Hematology Clinic of Atatürk University Faculty of Medicine Hospital and 30 healthy individuals. The demographic characteristics, hemogram and biochemical parameters, performance scores, flow cytometry results, cytogenetic and molecular laboratory findings, follow-up durations, survival statuses, chemotherapy protocols, and patients' responses to chemotherapy were recorded. Serum-soluble endoglin was measured before and after chemotherapy in AML patients.Serum-soluble endoglin levels in AML patients before and after treatment were not significantly different (p = 0.494). The pretreatment serum-soluble endoglin (CD105) levels in AML patients were similar to those of the control group (p = 0.264). Endoglin (CD105) levels in the group that achieved remission after induction therapy and the refractory group were not significantly different (p = 0.245). Serum-soluble endoglin (CD105) levels were also similar between surviving patients and those who died (p = 0.07).Serum-soluble endoglin (CD105) levels may not hold diagnostic or prognostic significance in AML patients.
Keywords: acute myeloid leukemia; biomarker; serum-soluble endoglin; CD105; prognosis